Efficacy of premedication on post-endodontic pain: An umbrella review - S. Waje; R. D. Rao; A. Jain; S. S. Sachdev; P. Shah; T. Nemade (Эндодонтия Today, 2024)
AIM. To comprehensively analyze the information generated by earlier systematic reviews of studies on the effect of premedications on post-endodontic pain.METHODS. The systematic reviews published in the English language until 2023 were searched in the databases PubMed, Google Scholar, and Cochrane Library using the keywords were identified. from inception to August 2023. The methodological quality of the included articles was analyzed using AMSTAR 2 tool and ROBIS tool. The corrected covered area analysis was performed using the GROOVE tool.RESULTS. A total of n = 8 systematic reviews were identified. The included systematic reviews and meta analyses were conducted in the period 2018 to 2022. Two [25%] out of the eight included studies had meta analysis. According to the assessment of the AMSTAR 2 tool, one review had high quality, two reviews had moderate quality, two reviews had low quality, and three reviews had critically low quality. ROBIS analysis showed that all the studies had a low risk of bias. The CCA analysis performed with the GROOVE tool showed a high overlap of 11% among all the included studies.CONCLUSION. Premedication was found to be effective as a means of reduction of post endodontic pain, especially for acute pulpitis. Corticosteroids were generally found to be more effective than NSAIDs. The use of piroxicam or prednisolone would be the premedication of choice. Oral premedication had better compliance and efficacy compared to other routes of administration, although the onset of action and sustenance of the latter was superior.